The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1440-1746.2007.05061.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TXA2 synthesis with OKY‐046 improves liver preservation by prolonged hypothermic machine perfusion in rats

Abstract: The results demonstrate that TXA(2) is involved in the development of hepatocellular injury induced by HMP, and inhibition of TXA(2) synthesis during preservation and reperfusion protects liver hepatocytes and sinusoidal endothelial cells from injuries caused by prolonged HMP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…A number of animal studies have demonstrated that ozagrel is protective against various forms of trauma and disease, including lung injury [23,33], bronchial asthma [22,40] and ischemia/reperfusion-induced organ injury [41,42]. Ozagrel promptly inhibits TXA 2 synthase in vitro and in vivo [31].…”
Section: Discussionmentioning
confidence: 99%
“…A number of animal studies have demonstrated that ozagrel is protective against various forms of trauma and disease, including lung injury [23,33], bronchial asthma [22,40] and ischemia/reperfusion-induced organ injury [41,42]. Ozagrel promptly inhibits TXA 2 synthase in vitro and in vivo [31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hepatic ischemia leads to a detrimental metabolic cascade preceded by a decrease in oxidative phosphorylation, leading to ATP depletion, an increase in anaerobic metabolism, hepatocyte acidosis, dysregulation of ATP-dependent ion exchange mechanisms, mitochondrial dysfunction, cellular swelling, and death ( 21 , 22 ). Moreover, damage to the sinusoidal endothelial cells also leads to damage of hepatic microcirculation—moderated by, among others, the release of thromboxane A2, which plays an important role in liver dysfunction after implantation ( 23 ). Although this complex process is still not fully elucidated, it is known that hepatic ischemia is a key determinant in the development of early allograft dysfunction and negative post-transplant outcomes ( 24 ).…”
Section: Importance Of Graft Preservation and Overview Of Dynamic Pre...mentioning
confidence: 99%
“…Previous experimental studies on animal models support this idea. Xu et al ( 23 ) added a specific thromboxane A2 synthase inhibitor to the perfusate during HMP. The authors found that grafts in the study group demonstrated reduced portal pressure during reperfusion, lower lactate dehydrogenase levels in the perfusate, and significant improvement in tissue edema and hepatocellular necrosis ( 23 ).…”
Section: Graft Modification: Possibilities Beyond the Horizonmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the strategies used in organ transplants to minimize the injury caused by ischemia is hypothermia. It decreases the cellular components degradation, which is essential for cell viability, enzymatic reactions speed and cell death occurrence, also prevents intracellular acidosis [1][2][3] . This cold-induced down regulation of the metabolism protects the graft against reactive species of oxygen, during reperfusion 2, 4 .…”
Section: Introductionmentioning
confidence: 99%